Developing a valid scale of past tornado experiences - Demuth, Julie L., author; Trumbo, Craig, advisor; Long, Marilee, committee member; Morss, Rebecca, committee member; Most, David, committee member; Peek, Lori, committee member; Zimmerman, Donald, committee member (Colorado State University. Libraries, 2015)
People's past experience with a hazard theoretically is a key factor in how they perceive a future risk because experience is a mechanism through which one acquires knowledge about a risk. Despite this, past hazard experience has been conceptualized and measured in wide-ranging and often simplistic ways by researchers, resulting in mixed findings about the relationship between experience and risk perception. Thus, dimensions of past hazard experiences are not validly known, nor is it known how one's experiences relate to their assessment of future risks. Past hazard experience is particularly relevant in the context of weather risks, which are common enough for people to acquire many experiences. This dissertation presents the results of a study to develop a valid scale of past experiences in the context of tornado risks. The scale is developed by, first, conceptualizing and identifying dimensions of past tornado experience, and subsequently by examining the relationship between the different experience dimensions and people's tornado risk perception. Data were collected through two mixed-mode (Web+mail) surveys of the public who reside in tornado-prone areas. An initial set of items to measure people's most memorable tornado experience as well as their experiences with multiple tornado threats were developed and evaluated with the first survey. Additional aspects of people's past tornado experiences were elicited in their own words to identify potentially important ideas that were not captured in the original item set. The item set then was revised and evaluated with the second survey. The second survey also included a scale to measure people's cognitive-affective tornado risk perceptions. Six latent dimensions of people's past tornado experiences emerged from this study: most-memorable experience-related risk awareness, risk personalization, personal intrusive impacts, and vicarious troubling impacts, as well as multiple experiences with common personal threats and impacts and negative emotional responses. Risk awareness captures the event-specific awareness by the respondent and from social cues about the possibility of the hazard occurring and concern about it causing harm. Risk personalization captures one's protective and emotional responses as well as direct visual, auditory, and tactile sensory inputs of the hazard. Personal intrusive impacts capture unwelcome thoughts, feelings, and disruption caused by the hazard. Vicarious troubling impacts capture the tangible property damage and loss incurred by others, disruption to others, and others' verbal accounts of their experiences. Common personal threats and impacts capture the amount of experiences one has with official tornado warnings and sirens and with news coverage about tornado events and their impacts. Finally, negative emotional responses capture the amount of experience one has fearing and worrying due to tornadoes. Subsequently, these different dimensions were shown to have varying influences on cognitive, affective, and overall tornado risk perception. Personal intrusive impacts had a pervasive effect, enhancing each of the risk perception dimensions with especially strong influences on affective and overall risk perception. Risk awareness and risk personalization influenced cognitive and overall risk perception, but only when combined with the other experience dimensions, suggesting that these experiences may be made more salient when joint with others. Overall, this research theoretically advances how past experience is conceptualized and how it relates to risk perception, and it serves as a foundation for future theoretical and applied research that could leverage and extend this work.